Impact of Delirium and Suture-Less Securement on Accidental Vascular Catheter Removal in the ICU. Issue 4 (July 2014) - Sundararajan, K.; Wills, S.; Chacko, B.; Kanabar, G.; O'Connor, S.; Deane, A.M.
The objectives were to describe the incidence of accidental vascular catheter removal (AVCR) in an Australian Intensive Care Unit (ICU) and evaluate whether the fixation method or patient delirium increased the risk of AVCR. This prospective observational study was based in a tertiary level ICU between April 2011 and October 2012. All vascular catheters were secured either by sutures or by a suture-less securement device (STATLOCK™, Bard Medical, Covington, GA, USA) as per the treating clinician. Data were obtained from bedside nursing staff, with daily screening for delirium completed by the ICU medical team using the Confusion Assessment Method-ICU. 2361 patients were admitted during this period with 1032 patients screened and data available for 322 patients (452 vascular catheters). AVCR occurred in 15 patients (16 vascular catheters) (5.0%) with an incidence of AVCR of 2.77 per 100 catheter-days. Delirious patients were 13-fold more likely to have an AVCR event (odds ratio=13.3; 95% confidence interval 4.36, 40.52; P <0.0001). There was a non-significant trend to an increase in AVCR when using the suture-less securement device (odds ratio=2.6; 95% confidence interval 0.87, 7.8; P =0.09) but delirious patients were no more likely to have an AVCR episode when a suture-less securement device was used ( P =0.95). In this study the use of suture-less securement did not seem to increase the risk of AVCR. However, there was a non-significant trend towards increased AVCR when using suture-less securement devices, which may reflect a β error.